The potential benefit of a hybrid operating environment among severely injured patients with persistent hemorrhage: How often could we get it right?. Issue 3 (March 2016) - Fehr, Adam; Beveridge, Julie; D'Amours, Scott D.; Kirkpatrick, Andrew W.; Ball, Chad G.
Abstract : BACKGROUND: Selecting the appropriate initial destination (operating theater [OR], angiography suite, or intensive care unit [ICU]) in persistently hypotensive injured patients can be extremely challenging. The purpose of this study was to define the flow, interventions, and outcomes of these patients. METHODS: All persistently hypotensive (two or more systolic blood pressures < 90 mmHg) severely injured (Injury Severity Score [ISS] ≥ 12) adult patients (1995–2012) were analyzed over the first 24 hours at a Level I trauma referral center. Standard statistical methodology was used ( p < 0.05). RESULTS: Of 911 patients with an initial systolic blood pressure of less than 90 mm Hg (prehospital or initial trauma bay reading), 56% remained persistently hypotensive. These patients had a mean age of 41 years, were 73% male, and blunt injured in 87% of the cases. Initial destinations included the OR (53%), ICU (29%), trauma ward (13%) after resuscitation and diagnostic imaging, and interventional angiography suite (5%). Of all hypotensive patients, 67% received computed tomography either before or after initial transfer from the trauma bay. Of the patients who were moved to the OR, 64% were subsequently transferred to the ICU and 23% to the ward, and 14% died in the OR itself. Within the OR, 97% of the patients underwent an intervention (79% laparotomies). A total of 7% of the patients required both emergent operative and angiographic interventions. These were most commonly due to ongoing hemorrhage from pelvic fractures or major hepatic lacerations. Mortality was higher in patients who underwent operation before angiography (90% vs. 32%, p = 0.002). The median hospital length of stay was 22 days (ICU stay, 8 days). The mortality (<24 hours) of all persistently hypotensive patients was 22%. CONCLUSION: Up to 7% of patients in this cohort could benefit from the utility of a hybrid RAPTOR [Resuscitation with Angiography, Percutaneous Therapy Operative Repair] suite. A "direct to the RAPTOR suite" policy (i.e., bypass emergency department) must be used with caution. LEVEL OF EVIDENCE: Therapeutic study, level IV.